CLINICAL EFFICACY AND SAFETY OF THE DRUG NEUROOXIDOL-ZOMMER (250 MG/5 ML) IN PATIENTS WITH ISCHEMIC CEREBROVASCULAR ACCIDENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Objective of the study. To study the efficacy and safety of sequential therapy with Neurooxidol-Zommer (250 mg/5 ml), administered intravenously by drip for 14 days, in elderly patients with chronic cerebral ischemia (CCI) against the background of arterial hypertension and atherosclerosis. Material and methods. The open prospective observational study included 60 patients with an established diagnosis of CCI, confirmed by the results of neuroimaging. All patients were examined to assess the neuropsychological status (MoCA test), severity of asthenia (MFI-20 scale), emotional state (Hamilton Anxiety and Depression Scale), motor functions (Tinetti Formalized Clinical Scale for Assessing the Motor Activity of the Elderly). The effectiveness of the therapy was assessed using the quality-of-life questionnaire (SF-36). The study results showed high efficacy and safety of sequential therapy with Neurooxidol-Zommer (250 mg/5 ml) in relieving asthenic and emotional disorders, improving cognitive functions, and increasing the quality of life of patients. The maximum effect occurred after the completion of the full course of therapy. High patient compliance with the therapy and a low incidence of adverse events were shown. Sequential use of intravenous administration of Neurooxidol-Zommer (250 mg/5 ml) is an effective and safe method of treating patients with CCI.